2012
DOI: 10.1186/2049-6958-7-45
|View full text |Cite
|
Sign up to set email alerts
|

BMI can influence adult males’ and females’ airway hyperresponsiveness differently

Abstract: BackgroundEpidemiological data indicate that obesity is a risk factor for asthma, but scientific literature is still debating the association between changes in body mass index (BMI) and airway hyperresponsiveness (AHR).MethodsThis study aimed at evaluating the influence of BMI on AHR, in outpatients with symptoms suggestive of asthma.4,217 consecutive adult subjects (2,439 M; mean age: 38.2±14.9 yrs; median FEV1 % predicted: 100 [IQR:91.88-107.97] and FEV1/FVC % predicted: 85.77% [IQR:81.1-90.05]), performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…This means that a BMI increase determines functional alterations consistent with an obstructive pattern in female adolescents. This is in accordance with a previous study of ours, carried out on adults, where we found a significant reduction of FEV 1 /FVC ratio only in females with moderate AHR [ 20 ]. Also other researchers found a FEV 1 /FVC reduction both in obese children [ 6 ] and adults [ 36 ], though this was not confirmed by other authors [ 32 , 37 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This means that a BMI increase determines functional alterations consistent with an obstructive pattern in female adolescents. This is in accordance with a previous study of ours, carried out on adults, where we found a significant reduction of FEV 1 /FVC ratio only in females with moderate AHR [ 20 ]. Also other researchers found a FEV 1 /FVC reduction both in obese children [ 6 ] and adults [ 36 ], though this was not confirmed by other authors [ 32 , 37 ].…”
Section: Discussionsupporting
confidence: 94%
“…The risk evaluation in the two sexes showed that it was 38% greater in females when compared to males. This means that obesity influences only female adolescents and not male adolescents or children, which is perfectly in line with what was assessed in another study of ours [ 20 ] and in previous researches [ 23 , 25 , 26 ] where a higher AHR risk was observed only in adult females. Female adolescents become adults more precociously than males.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…35 Likewise, obesity was not associated with AHR in men, while such an effect was observed in women with moderate AHR. 36 In another study, sex had no effects on obesity -asthma association in children, but trunk predominant (central) adiposity was significantly associated with asthma only among women. 37 Overall, epidemiological studies suggest that the effects of obesity on asthma are greater in women, which seems to be related to the activity of estrogens.…”
Section: Sex Differencesmentioning
confidence: 95%
“…Obesity itself is not associated with airflow obstruction [29]. However, since obese individuals do breathe at lower lung volumes, the resulting airway narrowing may contribute to heightened airway hyperreactivity [3032], with one study noting the association only in females [33]. This latter observation may be due to a subgroup effect among the late-onset non-atopic obese asthma phenotype described above, as Dixon et al [34] demonstrated that obese asthmatics who had a low serum IgE (presumably late-onset of asthma) had improved airway hyperreactivity 12 months after bariatric surgery, but those with elevated serum IgE (presumably early onset of asthma) did not.…”
Section: Obesity and Airway Physiology In Asthmamentioning
confidence: 99%